A Pr3+ doping strategy for simultaneously optimizing the size and near infrared persistent luminescence of ZGGO:Cr3+ nanoparticles for potential bio-imaging. Issue 36 (19th July 2017) - Gong, Zheng; Liu, Yuxue; Yang, Jian; Yan, Duanting; Zhu, Hancheng; Liu, Chunguang; Xu, Changshan; Zhang, Hong
Abstract : The improved near infrared persistent luminescence of ZGGO:Cr 3+ nanoparticles achieved by adopting a Pr 3+ doping strategy facilitates deep tissue bio-imaging. Abstract : Spinel-phase Zn2 Ga2.98− x Ge0.75 O8 :Cr0.020, Pr x (ZGGO:Cr 3+, Pr 3+ ) near infrared (NIR) persistent luminescence nanoparticles (PLNPs) with different amounts of Pr 3+ dopant were prepared by a hydrothermal method in combination with a subsequent annealing in a vacuum. For these nanoparticles, the averaged particle size decreases from 64 to 37 nm with increasing Pr 3+ doping concentration from 0 to 0.025 and Cr 3+ and Pr 3+ ions are uniformly doped into the interior and surface of a single nanoparticle. It can be found that Pr 3+ doping leads to the appearance of more anti-site pairs ( ) around distorted octahedral Cr 3+ ions and enhanced NIR emissions around 697 nm, which originate from the 2 E( 2 G) → 4 A2 ( 4 F) and 4 T2 ( 4 F) → 4 A2 ( 4 F) transitions of the interior and surface Cr 3+ ions in the nanoparticles. In particular, for the interior Cr 3+ ions in the Pr 3+ doped nanoparticles, the enhanced NIR luminescence can be attributed to the suppressed energy transfer of the excited electrons from the 4 T2 ( 4 F) level to the trap level related to anti-site pairs ( ) around the distorted octahedral Cr 3+ ions. Our results suggest that Pr 3+ doped ZGGO:Cr 3+ PLNPs have potential applications for bio-imaging.